Potential Implication of Treatments for Alzheimer’s Disease: Current and Future - Jan Sudir Purba (PT Dexa Medica, 2023)
Alzheimer’s disease (AD) is a long-term and progressive neurodegenerative disorder, characterized by both structural abnormalities and inflammation in the brain. Patients suffering from AD lose their ability to perform daily activities, gradually worsens cognitive function and communicating skills, often accompanied by visual disturbances, eventually leads to disability. Pathologic characteristics of AD are β-amyloid (Aβ) plaque and neurofibrillary tangles. Current therapy available only targets to reduce symptoms using various drugs and psychotherapy, but do not cure the disease itself. Unfortunately, few chemical drugs designed for clinical applications have only reached the expected preventive therapeutic effect, with some safety concerns. Traditional herbal medicine has accumulated many experiences in the treatment of dementia during thousands of years and modern pharmacological studies have confirmed the therapeutic effects of many active components derived from herbal medicines. Recently, herbal medicine is shown to be a potential approach for various diseases, including neurodegenerative disorders.